RANCANG BANGUN MESIN LISTRIK PEMOTONG RUMPUT MENGGUNAKAN CONTROL ARDUINO - Sunardi; Giovani Toldo; Aripin Triyanto (CV. Multi Kreasi Media, 2024)
For land clearing from grass plants that surround the land, it is necessary to cut the grass. So the author here makes a prototype of a lawn mower using an Arduino control. This Arduino lawn mower uses a DC motor to drive the blades. The speed of the dc motor for this lawn mower is regulated by the L298N Driver programmed using an Arduino uno which can be adjusted using the keypad speed. The methods and procedures used are, field observations, planning, collecting materials, making portotypes, making Arduino programs and conducting experiments. The test results from this study indicate that this prototype works according to its design, where if humans use this tool it will be easier to adjust the speed of the lawn mower itself by pressing the keypad and it will automatically appear on the LCD with a PWM limit of NYS 225.